DIVERSITY OF MICROORGANISMS IN BIOGAS PRODUCTION THROUGH CO-DIGESTION OF CATTLE DUNG, POULTRY WASTE, AND PALM OIL MILL EFFLUENT - Ojetokun, Oluwaponmile; Bada, Babatunde; Atayese, Adijat Olabisi; Ojetokun, Olumide Joshua (FUDMA Journal of Sciences, 2025)
This study assessed microbial diversity in biogas production from co-digestion of cattle dung, poultry waste, and palm oil mill effluent (POME). The experiment used a batch feeding system with 28-day retention, examining six substrate treatments: (CD), (PW), (CD:PW 1:1), (CD: POME 1:1), (PW: POME 1:1), and (CD: PW: POME 1:1:2). pH and temperature were monitored using a pH/temperature meter, and biogas volume was measured by water displacement. The data underwent descriptive and inferential statistical analyses. The optimal co-digestion treatment of PW: POME (1:1) yielded the highest cumulative biogas volume (8.33 dm³) and peak production of 3.80 dm³ on day 14. Initial substrate analysis showed total viable bacterial counts of 6.35 × 105, 2.17 × 105, and 0.27 × 105 CFU/mL for CD, PW, and POME, respectively, while total viable fungal counts were 2.05 × 105, 3.25 × 105, and 3.05 × 105 CFU/mL. Microbial analysis identified four suspected bacterial species (Bacillus aquimaris, B. cibi, B. altitudinis, and B. cereus), five fungal species (Curvularia lunata, Aspergillus flavus, A. nidulans, A. aculeatus, and Trichoderma viride), and two yeast species (Candida albicans and C. tropicalis), with Bacillus and Aspergillus being dominant genera. The biogas slurry is rich in nutrients, particularly potassium, indicating potential as a biofertilizer. The co-digestion process promoted a diverse microbial community dominated by Bacillus and Aspergillus species, which enhance substrate breakdown and biogas production.